Betrayed : how the education establishment has betrayed America and what you can do about it - Rogers, Laurie H., 1961- (Rowman & Littlefield Education, 2010)
Betrayed aims to tell the truth of public education - from the perspective of a parent who has fought the education bureaucracy.